Pendampingan dan Pengembangan Produk Udeng Sangga Braja dalam Rangka Melestarikan Ciri Khas Kota Batu - Deniar, Shannaz Mutiara; Pratika, Yeyen; Effendi, Tonny Dian (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
This community service program focuses on mentoring and developing small business based on culture. The partner of this activity is Paguyuban Sangga Braja which is located in Batu City. Paguyuban Sangga Braja has a cultural product called as udeng or the typical headband of Batu City. This udeng is designed with an emphasis on the history, philosophy and local wisdom of Batu City which also aims to become a traditional characteristic of Batu City. The problem faced by partner is that partner has an expectation that this cultural product will become a characteristic of Batu City, unfortunately people of Batu City are still not aware with the existence of this udeng. So, problem focus in this program is related to the marketing of this udeng in Batu City so that it is better known by public. To overcome this problem, the community service team helps partner in terms of assistance and improvement from the marketing aspect. Visual video and booklet used were chosen as the right alternative at that moment because it can be used to inform people about the existence of udeng and increase public awareness of this product in Batu City. In addition, the team also provided assistance to the IPR registration so that the copyright of Udeng could be more secure. The results of this community service show quite good results with video and booklet containing the philosophy and ways of using udeng as a marketing medium and an IPR certificate to protect the copyright of this udeng.DOI:Â https://doi.org/10.26905/abdimas.v6i2.5171